2003
DOI: 10.1046/j.1538-7836.2003.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

What is all that thrombin for?

Abstract: Summary. The hemostatic process initiated by the exposure of tissue factor to blood is a threshold limited reaction which occurs in two distinct phases. During an initiationphase, small amounts of factor (F)Xa, FIXa and thrombin are generated. The latter activates the procofactors FV and FVIII to the activated cofactors which together with their companion serine proteases form the intrinsic FX activator (FVIIIa-FIXa) and prothrombinase (FVa-FXa) which generate the bulk of FXa and thrombin during a propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
385
0
18

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(413 citation statements)
references
References 68 publications
10
385
0
18
Order By: Relevance
“…This amount of thrombin appears to be sufficient for inducing normal fibrin polymerization and clot firmness. This finding is in accordance with the mathematical model developed by Mann et al32 who showed that tiny amounts of thrombin, appeared at the beginning of the initiation phase of coagulation, are required for normal fibrin polymerization. In the presence of fondaparinux at concentrations which induced comparable inhibition of thrombin generation as rivaroxaban, although the minimum thrombin generation was preserved, clot formation kinetics were altered.…”
Section: Discussionsupporting
confidence: 92%
“…This amount of thrombin appears to be sufficient for inducing normal fibrin polymerization and clot firmness. This finding is in accordance with the mathematical model developed by Mann et al32 who showed that tiny amounts of thrombin, appeared at the beginning of the initiation phase of coagulation, are required for normal fibrin polymerization. In the presence of fondaparinux at concentrations which induced comparable inhibition of thrombin generation as rivaroxaban, although the minimum thrombin generation was preserved, clot formation kinetics were altered.…”
Section: Discussionsupporting
confidence: 92%
“…Efficient prothrombin activation by prothrombinase is essential for generating a burst of thrombin at sites of vascular injury (50). For efficient activation to occur, prothrombin must incorporate into the prothrombinase complex.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in the presence of platelets and tissue factor bearing cells suggest that, as soon as such structures are present, physical transport through diffusion might play a role in determining thrombin generation velocities [5,6,7]. In coagulation experiments in plasma in vitro, procoagulant phospholipids are added to platelet-poor plasma (PPP) in the form of vesicles; in plateletrich plasma (PRP), they are provided by activated platelets [8].At the moment that a clot forms, $98% of thrombin is still to be generated [9,10]. The total amount of thrombin formed is an important determinant of the quality of hemostasis or the extent of thrombosis [11] and this thrombin is almost all formed within the fibrin mesh of the clot.…”
mentioning
confidence: 99%